1995
DOI: 10.1002/pen.760351907
|View full text |Cite
|
Sign up to set email alerts
|

Mixing in reactive extrusion of low‐density polyethylene melts: Linear vs. branched

Abstract: The melt flows of linear low‐density polyethylene (LLDPE) and branched low‐density polyethylene (LDPE) have been compared in a fully intermeshing co‐rotating twin‐screw extruder. The polyethylene melts were selected in order to investigate the effects of the melt rheology on the mixing. Their shear vicosity curves are quite similar, but the LDPE has a markedly higher apparent extensional viscosity over a wide range of stretch rates. The stagger of the paddles in the mixing zone of the extruder creates axial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Chen et al27 found that a polymer with lower viscosity (higher melt flow index) had longer t, but its axial mixing (dispersion) quality was not affected by viscosity. Polance and Jayaraman13 revealed that polymers with lower extensional viscosity had shorter t and better axial mixing quality. In the present study, we investigated t and Pe number (the latter being a measure of the axial mixing quality), given by eqs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al27 found that a polymer with lower viscosity (higher melt flow index) had longer t, but its axial mixing (dispersion) quality was not affected by viscosity. Polance and Jayaraman13 revealed that polymers with lower extensional viscosity had shorter t and better axial mixing quality. In the present study, we investigated t and Pe number (the latter being a measure of the axial mixing quality), given by eqs.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the RTD of pure polymers in TSE was widely investigated 4, 12–16. Its variation as a function of processing parameters, geometry of the equipment, and polymer properties (such as shear or extensional viscosity, elasticity, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Chain extenders have been widely used to improve the rheological properties of polyesters by reacting with either the carboxylic acid and/or hydroxyl end groups. The blown film process requires polymer melts to exhibit a certain level of melt strength as well as nonlinear viscoelastic properties like strain hardening.…”
Section: Introductionmentioning
confidence: 99%
“…Long-chain branching or a small fraction of high-molecular-weight polymer can be introduced to neat PLA to improve these rheological properties. 2,3 Chain extenders have been widely used to improve the rheological properties of polyesters by reacting with either the carboxylic acid and/or hydroxyl end groups. For example, diisocyanates have proven to be an effective chain extender of PLA and improve its rheological properties.…”
Section: Introductionmentioning
confidence: 99%